Classification of hand postures using forearm perimeter sensor and compensation of residual muscle volume change with sEMG. (1st January 2014) - Choi, Hwiyong; Lee, Sangyoon
This paper reports that performance of a sensor for measuring perimeter change of the forearm has been improved by compensating for residual muscle volume change. A key idea of the compensation is removing offset signal during the muscle relaxed state. One channel of surface electromyography (sEMG) signal was employed for detecting the muscle activity. The suggested method was validated by online classification of three different hand postures with one forearm perimeter sensor. The result shows that the suggested method compensates for residual muscle volume change effectively and improves accuracy of hand posture classifier.